Host in the period supervised curriculum internship in Physical Education (Research, Society and Development, 2021)
Introduction: The Supervised Curriculum Internship (SCI) is a curricular component of undergraduate courses and a fundamental period of initial training for future teachers. Among its actors, the intern and the Supervisor Teacher (ST) stand out. Objective: Analyze and describe the situations observed in the experiences and interactions between the ST and its intern at school, based on experiences in the Elementary School SCI. Methodology: This study is part of a Master's thesis in Physical Education. A qualitative research approach, with a descriptive character and using the observational method. For data collection, on-site observation was carried out with Field Notes, in a school in the Public Teaching Network in the Municipality of Seropédica/Rio de Janeiro. The sample consisted of a ST and her intern. Results: The relationship established between the ST and the intern was marked by cooperation, interaction, exchange and collaboration, evidencing characteristics of a reception carried out by the ST. However, it was observed that the strategies adopted by the ST happened in an intuitive way, possibly due to the lack of guidance and knowledge about their attributions. Final considerations: The importance of specific, grounded and contextualized training for the ST is emphasized, in order to support supervisory actions at school. Still, the need for greater partnership between university and school is alerted.